Reading children : essays on children's literature - Gupta, Nilanjana; Chatterjee, Rimi B. (New Delhi : Orient Blackswan, 2009)
Contributed articles.
Includes index.
Includes bibliographical references (p. [193]-195).
Keywords: Children's literature -- History and criticism